A New Rash Differential: CoVID-19. (January 2021) - Gooch, Michael D.
Abstract : The CoVID-19 pandemic has impacted all areas of health care, especially emergency medicine. Most commonly, CoVID-19 is associated with respiratory and typical viral presentations. However, nonrespiratory presentations are becoming more common. Reported CoVID-19 dermatological changes include maculopapular and urticarial rashes, chilblain-like and livedo reticularis discolorations, and less commonly vesicular and petechial rashes. As frontline clinicians, emergency nurse practitioners should be aware of these skin findings to recognize potentially infected and otherwise asymptomatic patients. Early recognition could potentially lead to an earlier diagnosis and limit the spread of severe acute respiratory syndrome coronavirus 2.